ANALISIS PENGARUH TINGKAT SUKU BUNGA (SBI), NILAI TUKAR (KURS) RUPIAH, INFLASI, DAN INDEKS BURSA INTERNASIONAL TERHADAP IHSG (STUDI PADA IHSG DI BEI PERIODE 2008-2012) - Ria Astuti; Apriatni Endang Prihatini; Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to test the influence of Interest Rate (SBI), Exchange Rate of Rupiah, Inflation, and International Exchange Index (Nikkei 225 Index and Hang Seng Index) on Composite Stock Price Index in The Period 2008-2012. Analytical techniques used were linear regression, while hypothesis test used t - test and F - test with significance level of 5%. The classical assumptions test used in this study include normality, multicollinearity, heteroscedasticity and autocorrelation test. The research prove that Interest Rate (SBI) and Exchange Rate of Rupiah had a negative effect and significant to Composite Stock Price Index, Inflation had a negative effect and not significant to Composite Stock Price Index Meanwhile, Nikkei 225 Index and Hang Seng Index had a positive and significant effect to Composite Stock Price Index.